RELEVANSI KONSELING ISLAM DENGAN TERAPI KESEHATAN MENTAL PERSPEKTIF QUR'AN SURAT YUNUS AYAT 57 - Fauziah Fauziah; Hasan Zaini; Irman Irman (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
Mental health is a condition that allows a person to develop all aspects of his development, both physical, intellectual, and emotional, optimally and in harmony with the development of other people, thus enabling him to interact with the surrounding environment. Mental health disorders need to be corrected with Islamic counseling, which is a strategy implemented to guide people to strengthen their faith and belief in Islamic teachings in order to maintain mental health and live according to the provisions of the Al-Qur'an and the Sunnah of the Prophet Muhammad SAW. This research uses a research method in the form of a literature study. The results of the literature review based on the journals studied revealed that Islamic counseling guidance has relevance to mental health therapy from the perspective of Q.S. Yunus verse 57, where mental health therapy from the perspective of Q.S. Yunus verse 57 can be one of the techniques or approaches that can be used in Islamic counseling guidance.